Early-type galaxies in the Antlia Cluster: a deep look into scaling relations - Calderón, Juan Pablo (2015)
We present the first large-scale study of the photometric and structural relations followed by early-type galaxies (ETGs) in the Antlia cluster. Antlia is the third nearest populous galaxy cluster after Fornax and Virgo (d ∼ 35 Mpc). A photographic catalogue of its galaxy content was built by Ferguson & Sandage in 1990 (FS90). Afterwards, we performed further analysis of the ETG population located at the cluster centre. Now, we extend our study covering an area four times larger, calculating new total magnitudes and colours, instead of isophotal photometry, as well as structural parameters obtained through S ́ ersic model fits extrapolated to infinity. This work involves a total of 177 ETGs, out of them 56 per cent have been catalogued by FS90 while the rest (77 galaxies) are newly discovered ones. Medium-resolution GEMINI and Very Large Telescope (VLT) spectra are used to confirm membership when available. Including radial velocities from the literature, 59 ETGs are confirmed as Antlia members. Antlia scaling relations mainly support the existence of unique functions (linear and curved) that join bright and dwarf ETGs, excluding compact ellipticals (cEs). Lenticular galaxies are outliers only with respect to the curved relation derived for effective surface brightness versus absolute magnitude. The small number of bright ellipticals and cEs present in Antlia, prevents us from testing if the same data can be fitted with two different linear sequences, for bright and dwarf ETGs. However, adding data from other clusters and groups, the existence of such sequences is also noticeable in the same scaling relations.